Iron-oxide minerals in the human tissues - Svobodova, H; Kosnáč, D; Tanila, H; Wagner, A; Trnka, M; Vitovič, P; Hlinkova, J; Vavrinsky, E; Ehrlich, H; Polák, Š; Kopani, M (Biometals, 2020)
Iron is critically important and highly regulated trace metal in the human body. However, in its free ion form, it is known to be cytotoxic; therefore, it is bound to iron storing protein, ferritin. Ferritin is a key regulator of body iron homeostasis able to form various types of minerals depending on the tissue environment. Each mineral, e.g. magnetite, maghemite, goethite, akaganeite or hematite, present in the ferritin core carry different characteristics possibly affecting cells in the tissue. In specific cases, it can lead to disease development. Widely studied connection with neurodegenerative conditions is widely studied, including Alzheimer disease. Although the exact ferritin structure and its distribution throughout a human body are still not fully known, many studies have attempted to elucidate the mechanisms involved in its regulation and pathogenesis. In this review, we try to summarize the iron uptake into the body. Next, we discuss the known occurrence of ferritin in human tissues. Lastly, we also examine the formation of iron oxides and their involvement in brain functions.
Keywords: železo; oxidy; Biomineralization; Neurodegenerative Diseases; mozek; Ferritins; ferritiny; Humans; Iron; Oxides; neurodegenerativní nemoci; lidé; Human tissues; Ferritin; Iron oxides; Brain